A Combined SNIFTIRS and XANES Study of Electrically Polarized Copper Electrodes in DMSO and DMF Solutions of Cyanate (NCO−), Thiocyanate (NCS−) and Selenocyanate (NCSe−) Ions. Issue 7 (2nd April 2015) - Alwis, L. K. H. K.; Mucalo, Michael R.; Ingham, Bridget; Kappen, Peter
Abstract : A SNIFTIRS (subtractively normalized interfacial Fourier transform infrared spectroscopy) and X-ray absorption spectroscopy (XAS) study of electrically polarized copper electrodes in six polar aprotic solvent-based systems is presented. In the systems investigated, i.e. dimethyl formamide (DMF) and dimethyl sulfoxide (DMSO) solutions containing pseudohalide species of cyanate (NCO − ), thiocyanate (NCS − ) and selenocyanate (NCSe − ) codissolved with tetrabutylammonium perchlorate (TBAP), Cu was found to dissolve over a wide range of potentials to produce the corresponding Cu(I) pseudohalide and/or Cu(II) pseudohalide complex ion species. Insoluble deposited films were also observed at higher anodic applied potentials, thought to be CuSCN in the Cu/NCS − /DMSO or DMF systems, and solid K(SeCN)3 in the Cu/NCSe − /DMSO or DMF systems respectively. The presence of the Cu(II) and/or Cu(I) oxidation states in complexes formed by polarization in Cu/pseudohalide ion systems in DMSO was clearly proven using XAS of cell solutions sampled after SNIFTIRS/electrical polarization experiments. In addition, Fourier transform infrared (FTIR) and X-ray absorption near edge spectroscopy (XANES) data obtained from model solutions prepared from mixing Cu(I) and/or Cu(II) salts with the respective pseudohalide ions in DMF and DMSO confirmed the speciation observed in the electrochemical experiments.